Analysis of Cost of Goods Produced as a Basis for Calculating the Selling Price of Semprong Pusaka Jaya Cilamaya Products - Saleh, Intan Noviantika; Suherman, Enjang; Hidayaty, Dwi Epty (International Journal Labs, 2023)
The main objectives of this study are to ascertain, examine, analyze, and explain the production costs of Semprong Pusaka Jaya. (2) to ascertain, study, debate, and explain the process of determining the cost of goods by the Semprong Pusaka Jaya company using the overall costing approach. (3) know how to study, discuss, and explain how to calculate the cost of production to determine the selling price of the Semprong Pusaka Jaya business. The research method used is a type of quantitative descriptive research. Primary data in the form of interview data in the form of an analysis of the cost of production as the basis for determining the selling price of the product was collected directly from the company and used in this study. Regarding the secondary data used in this study collected from publications, websites, books, and other sources. The results of data analysis affect the selling price. Companies should use the whole costing strategy to determine the selling price of Semprong according to the cost plus percing method. In particular, the price per ball must be changed from Rp.18,000 to Rp. 20080 initially.